The Training Program Promoting Students’ Self-Realization in the Integrated Educational Environment - Kuprieieva, Olga (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article presents the training program (for personality-oriented training) developing psychological qualities and personal resources of students’ self-realization in the integrated educational environment: psychological hardiness, value-semantic and motivational resources (meaningfulness of life, motives for self-development, values of self-realization, time perspective); resources of self-regulation (self-attitude, self-efficacy, autonomy); active coping strategies. The study purpose was to reveal the content of the training program promoting students’ self-realization in the integrated educational environment and the features of its implementation. The correlation analysis was used to identify links among the components of self-realization of students with disabilities and their personal characteristics – self-attitudes, life values and meanings, basic beliefs, psychological hardiness, time perspective, used coping strategies. The comprehensive empirical study involved 325 students with disabilities and 225 students without disabilities studying in integrated university groups (Kyiv). The targets for psychological influence and meaningful parts of the proposed training promoting self-realization were identified. The training program was a personality-oriented training and included a set of psychological techniques and methods promoting continuous personal growth, activating psychological mechanisms of self-development, self-improvement, self-activation and self-realization of potential capabilities. The training program was developed on the principles of humanistic and positive psychology; the proactive conceptual model of disability; the resource-oriented approach used in psychological counselling and psychotherapy; the concept of self-determined behaviour. The purpose of the proposed training program was to promote students’ self-realization via development of their psychological qualities and personal resources: psychological hardiness, value-semantic and motivational resources (meaningfulness of life, motives for self-development, values of self-realization, time perspective); resources of self-regulation (self-attitude, self-efficacy, autonomy); active coping strategies. The training program was based on self-realization components selected by us and consisted of three meaningfully related parts: «I and my inner world» (psychological resources of personal self-realization) including three modules; «I and the Other» (social resources of personal self-realization) with two modules; «I am in the World and Life» (instrumental resources maintaining life quality and psychological well-being) with two modules. Approbation of the program has showed its high efficiency. The analysed components of students’ self-realization – psychological hardiness, self-attitude, self-acceptance, meaningful life goals, active coping – showed their significant growth, and as a consequence, improved students’ psychological well-being.